Analysis of the Annealing Budget of Metal Oxide Thin‐Film Transistors Prepared by an Aqueous Blade‐Coating Process. (12th December 2022) - Tang, Tianyu; Dacha, Preetam; Haase, Katherina; Kreß, Joshua; Hänisch, Christian; Perez, Jonathan; Krupskaya, Yulia; Tahn, Alexander; Pohl, Darius; Schneider, Sebastian; Talnack, Felix; Hambsch, Mike; et al.
Abstract: Metal oxide (MO) semiconductors are widely used in electronic devices due to their high optical transmittance and promising electrical performance. This work describes the advancement toward an eco‐friendly, streamlined method for preparing thin‐film transistors (TFTs) via a pure water‐solution blade‐coating process with focus on a low thermal budget. Low temperature and rapid annealing of triple‐coated indium oxide thin‐film transistors (3C‐TFTs) and indium oxide/zinc oxide/indium oxide thin‐film transistors (IZI‐TFTs) on a 300 nm SiO2 gate dielectric at 300 °C for only 60 s yields devices with an average field effect mobility of 10.7 and 13.8 cm 2 V −1 s −1, respectively. The devices show an excellent on/off ratio (>10 6 ), and a threshold voltage close to 0 V when measured in air. Flexible MO‐TFTs on polyimide substrates with AlOx dielectrics fabricated by rapid annealing treatment can achieve a remarkable mobility of over 10 cm 2 V −1 s −1 at low operating voltage. When using a longer post‐coating annealing period of 20 min, high‐performance 3C‐TFTs (over 18 cm 2 V −1 s −1 ) and IZI‐TFTs (over 38 cm 2 V −1 s −1 ) using MO semiconductor layers annealed at 300 °C are achieved. Abstract : Advances toward an eco‐friendly, streamlined method for preparing metal oxide thin‐film transistors via a pure water‐based solution blade‐coating process with focus on low temperature and rapid annealing treatment are reported. This work demonstrates that despite the emphasis on greener fabrication, by combining these fabrication elements device performance does not have to be sacrificed.